Solar System Courseware for Dyslexia Children / Puteri Nur Anserra Anuar - Anuar, Puteri Nur Anserra (2022)
The development of Solar System Courseware for Dyslexia Children also known as SSCDC is to assist children with reading disabilities also known as dyslexia especially, children who have phonological dyslexia to learn how to read and write the names of star and planets in our solar system. In this project, three objectives have been identified that is to identify the current phonological characteristics of courseware for children with dyslexia, to design and develop the courseware for children with dyslexia to learn about the solar system, and lastly to evaluate the functionality of the proposed courseware. The theory used to develop this courseware applies the Fogg Behaviour model (FBM) persuasive technology to encourage the children to act based on targeted behaviour, hoping to attract their attention during the learning session and allowing teachers to make the courseware as one of their teaching materials. To develop this courseware, the Addie model, a methodology, has been chosen to assist this project in reaching the objectives successfully. To determine the courseware efficiency and effectiveness, functionality testing and usability testing using test cases have been made to ensure the purposes of the project are achieved. The developer also acts as a tester that fills in the test case form for the courseware’s multimedia elements such as graphics, audio, video, text, animation, and the flow of the courseware follow the expected outcome to ensure the content of multimedia is delivered. Hopefully, this courseware can help children with phonological dyslexia to learn to read and write better and spark their interest in learning about our solar system.